Molecular-Network Transformations in Tetra-Arsenic Triselenide Glassy Alloys Tuned within Nanomilling Platform - Oleh Shpotyuk; Malgorzata Hyla; Yaroslav Shpotyuk; Zdenka Lukáčová Bujňáková; Peter Baláž; Pavlo Demchenko; Andrzej Kozdraś; Vitaliy Boyko; Andriy Kovalskiy (Molecules, 2024)
Polyamorphic transformations driven by high-energy mechanical ball milling (nanomilling) are recognized in a melt-quenched glassy alloy of tetra-arsenic triselenide (As4Se3). We employed XRPD analysis complemented by thermophysical heat-transfer and micro-Raman spectroscopy studies. A straightforward interpretation of the medium-range structural response to milling-driven reamorphization is developed within a modified microcrystalline model by treating diffuse peak-halos in the XRPD patterns of this alloy as a superposition of the Bragg-diffraction contribution from inter-planar correlations, which are supplemented by the Ehrenfest-diffraction contribution from inter-atomic and/or inter-molecular correlations related to derivatives of thioarsenide As4Sen molecules, mainly dimorphite-type As4Se3 ones. These cage molecules are merely destroyed under milling, facilitating the formation of a polymerized network with enhanced calorimetric heat-transfer responses. Disruption of intermediate-range ordering, due to weakening of the FSDP (the first sharp diffraction peak), accompanied by an enhancement of extended-range ordering, due to fragmentation of structural entities responsible for the SSDP (the second sharp diffraction peak), occurs as an interplay between medium-range structural levels in the reamorphized As4Se3 glass alloy. Nanomilling-driven destruction of thioarsenide As4Sen molecules followed by incorporation of their remnants into a glassy network is proved by micro-Raman spectroscopy. Microstructure scenarios of the molecular-to-network polyamorphic transformations caused by the decomposition of the As4Se3 molecules and their direct destruction under grinding are recognized by an ab initio quantum-chemical cluster-modeling algorithm.